Contact Points Between the Austrian School and Biblical Christianity in the Debate Concerning Fair Prices - Martins, Yago (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2016)
The subject of fair prices is addressed by the tradition of Christian thought and by the axiological approaches provided by the Austrian School of Economics. Through the presentation and discussion of the biblical perspective regarding fair prices, as well as through reflexions by prominent authors of scholastic economic thought and the Austrian School of Economics, I address and analyze the contact points between the Austrian School and biblical Christianity about the subject.